Modulation of α5 Subunit‐Containing GABAA Receptors Alters Alcohol Drinking by Rhesus Monkeys. (5th November 2012) - Rüedi‐Bettschen, Daniela; Rowlett, James K.; Rallapalli, Sundari; Clayton, Terry; Cook, James M.; Platt, Donna M.
Abstract : Background: Alcohol's ability to potentiate the activity of γ‐aminobutyric acid (GABA) at GABAA receptors has been implicated as a key mechanism underlying the behavioral effects of alcohol. The complex molecular biology of these receptors raises the possibility that particular receptor subtypes may play unique roles in alcohol's abuse‐related effects and that subtype‐selective ligands with therapeutic specificity against alcohol might be developed. This study evaluated the capacity of α5GABAA receptor ligands to alter selectively the reinforcing effects of alcohol. Methods: Two groups of rhesus monkeys were trained to orally self‐administer alcohol or sucrose under fixed‐ratio schedules and limited daily access conditions. In addition, following daily self‐administration sessions, the behavior of each monkey was scored for both species‐typical and drug‐induced behaviors. Results: Concentrations of 1 to 6% alcohol maintained self‐administration above water levels, engendered pharmacologically relevant blood alcohol levels ranging from 90 to 160 mg/dl, and produced changes in behavior typical of alcohol intoxication. Concentrations of 0.3 to 3% sucrose also reliably maintained self‐administration. The α5GABAA receptor agonist QH‐ii‐066 enhanced and the α5GABAA receptor inverse agonist L‐655, 708 inhibited alcohol, but not sucrose drinking. The changes in alcohol drinking could be reversed with the α5GABAA receptor antagonist XLi‐093. However, L‐655, 708 increased yawning in both alcohol and sucrose drinkers, possibly indicative of an anxiogenic effect. Conclusions: These findings suggest a prominent and specific role for α5GABAA receptor mechanisms in the reinforcing effects of alcohol. Moreover, these results suggest that α5GABAA receptors may represent a novel pharmacological target for the development of medications to reduce drinking. Of ligands modulating this receptor, α5GABAA receptor inverse agonists may hold the most promise as alcohol pharmacotherapies.